L’émeute de Lachine en 1812: la coordination d’une contestation populaire - Dessureault, Christian (Revue d'histoire de l'Amérique française, 2008)
issued: 2008-23-00
Keywords: Lachine; Émeutes

Le lock-out de La Presse et l'émeute du 29 octobre 1971: un conflit d'envergure nationale - Ménard, Yves (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 2002)
issued: 2002-23-00
Keywords: Presse (La); Émeutes

L'émeute inventée - Jackson, James (VLB, 2014)
Keywords: Armée; Irlandais; Tracey; Daniel; Émeutes

L'émeute des fémurs: contestations étudiantes, dissections humaines et professionnalisation de la médecine au Québec - Robert, Martin (Canadian Historical Review, 2021)
Number: 4
Keywords: Criminalité; Médecine; Émeutes; Étudiants

L'émeute Gavazzi: violence et liberté d'expression au milieu du XIXe siècle - Breton, Vincent (Bulletin d'histoire politique, 2006)
issued: 2006-24-00
Keywords: Gavazzi; Alessandro; Irlandais; Protestants; Émeutes

L’émeute Gavazzi: pouvoir et conflit religieux au Québec au milieu du 19e siècle - Breton, Vincent (Université du Québec à Montréal, 2004)
Keywords: Gavazzi; Alessandro; Irlandais; Protestants; Émeutes

Une émeute incendiaire: la destruction du parlement à Montréal (25 avril 1849) - Roussin, Éric (Histoire Québec, 2016)
Number: 2
Keywords: Anglophones; Francophones; Incendies; Parlement; Émeutes

L’émeute des tramways de Montréal (1955) et la mauvaise conduite des étudiants: un cas d’appropriation de l’espace urbain - Poitras, Daniel (Urban History Review / Revue d'histoire urbaine, 2018)
issued: 2018-23-00/2019-21-00
Keywords: Association générale des étudiants de l'Université de Montréal; Associations étudiantes; Délinquance; Tramways; Transport en commun; Université McGill; Université de Montréal; Émeutes; Étudiants

Analyse comparée méthodologique du traitement journalistique de l'événement du Lundi de la matraque, 24 juin 1968 - Ratté, Julie (Université de Sherbrooke, 2013)
Keywords: Émeutes

The Trials and Tribulations of Riot Prosecutions: Collective Violence, State Authority and Criminal Justice in Quebec, 1841-1892 - Fyson, Donald (Canadian State Trials. Vol 3: Political Trials and Security Measures, 1840-1914, 2009)
Keywords: Criminalité; Émeutes

"Shame upon you as men!" Contesting Authority in the Aftermath of Montreal’s Gavazzi Riot - Horner, Dan (Histoire sociale / Social History, 2011)
Number: 87
Keywords: Protestants; Émeutes

Parliament in Flames - Graham, Joseph (Canada's History, 2011)
issued: 2011-02/2011-03
Keywords: Incendies; Parlement; Émeutes

French Canadians and the Beginning of the War of 1812: Revisiting the Lachine Riot - Mills, Sean (Histoire sociale / Social History, 2005)
Historians have generally claimed that, during the War of 1812, unlike in earlier periods, French Canadians eagerly rallied to the British cause and willingly fought to defend British North America from American invasion. Nearly all studies of French-Canadian participation in the war, however, focus on the Battle of Châteauguay in 1813, and few examine the first year of the war. A close look at French Canadians’ reactions to the outbreak of the War of 1812 would indicate that they were hardly unanimous in their support. A detailed study of the largest and most violent act of resistance — a riot that broke out at Lachine at the beginning of July 1812 — reveals some of the reasons why so many habitants refused to perform their militia duty.
Number: 75
Keywords: Guerre; Lachine; Émeutes

Of Bludgeons and Ballots: Political Violence, Municipal Enfranchisement, and Local Governance in Mid-Nineteenth-Century Montreal - Grittner, Colin (Violence, Order, and Unrest: A History of British North America, 1749-1876, 2019)
Keywords: Charte; Élections; Émeutes

'Riots' at Sir George Williams: Construction of a Social Conflict in the Sixties - Martel, Marcel (Debating Dissent: Canada and the Sixties, 2012)
Keywords: Université Sir George Williams; Émeutes

After the Fire Comes the Investigation. Citizens Give Testimony - Roy, Alain; Horner, Dan (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n297 Translators: _:n62302
Keywords: Incendies; Parlement; Torys; Émeutes

1849. To the Parliament House! - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n285 Translators: _:n62325
Keywords: Incendies; Parlement; Torys; Émeutes

Après l'incendie, l'enquête. Des citoyens témoignent - Horner, Dan (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Incendies; Parlement; Torys; Émeutes

1849. Tous au parlement! - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Incendies; Parlement; Torys; Émeutes

La session ardente. Fureur et violences au Parlement en 1849 - Gallichan, Gilles (Les Cahiers des Dix, 2008)
Number: 62
Keywords: Incendies; Parlement; Torys; Émeutes

The Riot that Never Was: The Military Shooting of Three Montrealers in 1832 and the Official Cover-Up - Jackson, James (Baraka Books, 2009)
Keywords: Armée; Irlandais; Tracey; Daniel; Émeutes

L'hostilité entre Irlandais catholiques et Irlandais protestants. La Saint-Barthélemy de Montréal (1853) - Germain, Jean-Claude (Montréal en tête, 2013)
issued: 2013-23-00
Keywords: Gavazzi; Alessandro; Irlandais; Protestants; Émeutes

La nuit de feu des livres et des archives du Parlement - Gallichan, Gilles (Bulletin d'histoire politique, 2013)
issued: 2013-23-00
Keywords: Archives; Incendies; Parlement; Torys; Émeutes

Le 21 mai 1832, sur la Rue du Sang - Boileau, Gilles (Histoire Québec, 2001)
Number: 3
Keywords: Bagg; Stanley; Tracey; Daniel; Élections; Émeutes

L'incendie du parlement et le manifeste annexionniste: la face cachée du torysme montréalais (1832-1849) - Deschamps, François (Bulletin d'histoire politique, 2013)
issued: 2013-23-00
Keywords: Incendies; Mouvement annexionniste; Parlement; Torys; Émeutes

In Response to the Unrest, Petitions in Support of the Queen Poured in. Denouncing the Tories to Save the Empire - Roy, Alain (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n263 Translators: _:n62291
Keywords: Incendies; Mouvement annexionniste; Parlement; Réformistes; Torys; Émeutes

Rebellion Losses Bill: Mere Pretext or the Real Cause of the Burning of Parliament - Leblanc, Jean-François (Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada, 2022)
Translators: _:n274 Translators: _:n62280
Keywords: Incendies; Parlement; Rébellions; Réformistes; Torys; Émeutes

Shame upon you as men!: Competing Visions of Masculine Authority in the Aftermath of Montreal's Gavazzi Riot - Horner, Dan (Gender History: Canadian Perspectives, 2014)
Keywords: Britanniques; Canadiens français; Gavazzi; Alessandro; Irlandais; Émeutes

Maurice Richard et la presse sportive montréalaise: l'itinéraire d'une passion partisane, 1942-1955 - Lapointe, Étienne (Université du Québec à Montréal, 2019)
Keywords: Canadien (Club de hockey); Hockey; Richard; Maurice; Émeutes

La loi sur l'indemnisation: simple prétexte ou véritable cause de l'incendie du parlement? - Leblanc, Jean-François (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Incendies; Parlement; Rébellions; Réformistes; Torys; Émeutes

En réponse à l'agitation: une pluie de pétitions de soutien à la reine. Dénoncer les torys pour sauver l'empire - Roy, Alain (Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada, 2021)
Keywords: Incendies; Mouvement annexionniste; Parlement; Réformistes; Torys; Émeutes

L'incendie du parlement (1849) et la presse britannique des deux côtés de l'océan - Deschamps, François (Montréal en tête, 2013)
issued: 2013-23-00
Keywords: Incendies; Montreal Gazette; Montreal Herald; Parlement; Émeutes

Montréal Capital City. The Remarkable History of the Archaeological Site of St Anne's Market and the Parliament of the Province of Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2022)
Translators: _:n461 Translators: _:n62043
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

The Rocket, the Riot, and the Revolution: Hockey in French Canada - Valentine, John; Toal, Brandon (Canadian Ethnic Studies / Études ethniques au Canada, 2021)
issued: 2021-23-00
Keywords: Canadien (Club de hockey); Hockey; Nationalisme; Richard; Maurice; Émeutes

Montréal capitale. L'exceptionnelle histoire du site archéologique du marché Sainte-Anne et du parlement de la province du Canada - Pothier, Louise (Pointe-à-Callière, cité d'archéologie et d'histoire de Montréal et Les Éditions de l'Homme, 2021)
Keywords: Archéologie; Incendies; Marchés; Parlement; Sainte-Anne (marché); Émeutes

From Self-Discipline to Self-Realization: Emotion Management in the Montreal Race Riots of 1969 and 2008 - Richter, Steve (Université Concordia, 2011)
Keywords: Latino-Américains; Montréal-Nord; Noirs; Université Sir George Williams; Émeutes

"Like a Thread of Gold". Tracing Alfred Perry's Lifelong Engagement with Montreal's Politics of Ethnic Confrontation - Horner, Dan (Engaging with Diversity. Multidisciplinary Reflections on Plurality in Quebec, 2018)
Keywords: Assurance; Gavazzi; Alessandro; Hôpital Douglas; Hôpitaux psychiatriques; Incendies; Parlement; Émeutes

Taking to the Streets: Crowds, Politics, and the Urban Experience in Mid-Nineteenth-Century Montreal - Horner, Dan (McGill-Queen's University Press, 2020)
Keywords: Grèves; Incendies; Lachine (canal); Parlement; Rues; Rébellions; Réformistes; Émeutes

Maurice Richard et la presse sportive montréalaise : l'itinéraire d'une passion partisane, 1942-1955 - Lapointe, Étienne (Université du Québec à Montréal, 2019)
Keywords: Canadien (Club de hockey); Devoir (Le); Hockey; Montreal Gazette; Montreal Star; Montréal-Matin; Richard; Maurice; Émeutes

Douze événements qui ont fait Montréal - Senez, Diane (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2017)
Number: 2
Keywords: Baseball; Capitulation; Chemins de fer; Crise d'octobre; Expos de Montréal (Montreal Expos); Expositions; Front de Libération du Québec; Grande Paix de Montréal; Grèves; Jeux olympiques; Mouvement étudiant; Transport en commun; Émeutes